Correlation and sex differences between ankle and knee cartilage morphology determined by quantitative magnetic resonance imaging. Issue 11 (12th October 2004) - Eckstein, F; Siedek, V; Glaser, C; Al-Ali, D; Englmeier, K-H; Reiser, M; Graichen, H
Abstract : Objective: To study the correlation between ankle and knee cartilage morphology to test the hypothesis that knee joint cartilage loss in gonarthritis can be estimated retrospectively using quantitative MRI analysis of the knee and ankle and established regression equations; and to test the hypothesis that sex differences in joint surface area are larger in the knee than the ankle, which may explain the greater incidence of knee osteoarthritis in elderly women than in elderly men. Methods: Sagittal MR images (3D FLASH WE) of the knee and hind foot were acquired in 29 healthy subjects (14 women, 15 men; mean (SD) age, 25 (3) years), with no signs joint disease. Cartilage volume, thickness, and joint surface area were determined in the knee, ankle, and subtalar joint. Results: Knee cartilage volumes and joint surface areas showed only moderate correlations with those of the ankle and subtalar joint ( r = 0.33 to 0.81). The correlations of cartilage thickness between the two joints were weaker still ( r = −0.05 to 0.53). Sex differences in cartilage morphology at the knee and the ankle were similar, with surface areas being −17.5% to −23.5% lower in women than in men. Conclusions: Only moderate correlations in cartilage morphology of healthy subjects were found between knee and ankle. It is therefore impractical to estimate knee joint cartilage loss a posteriori in cross sectional studies by measuring the hind foot and then applying a scaling factor. Sex differences in cartilage morphology do not explain differences in osteoarthritis incidence between men and women in the knee and ankle.